Religious orientation of spouses as a factor of relations in interethnic marriage: psychological aspect - Вaлиевa А. Б.; Кaбaковa М. П. (ҚазҰУ Хабаршысы. Психология және әлеуметтану сериясы, 2018)
The article presents the results of the study of the psychological characteristics of marital relations in interethnic marriages. The relevance of the study is due to the high level of interethnic marriages in our country and in the world as a whole. In the interethnic marriage, the ethnic and religious identity of the spouses is one of the main factors determining their relationships, characteristics of the upbringing and development of the personality of children, the position of the family in social interaction. Interethnic marriages are an alliance of representatives of two cultures, different systems of values and perceptions. The article emphasizes the importance and definition of the type of religiosity of each of the spouses in the study of the characteristics of marital relationships. Specificity of national cultures based on ethnic characteristics and lifestyles of nations, to which the spouses are related, is manifested in interethnic marriages rather actively and is expressed at the level of everyday interaction. The conclusion of interethnic marriages between spouses of different religions is connected with overcoming stereotypes and requires the responsibility of the spouses. Interethnic marriage between people of different faiths changes the national and cultural origin of spouses under the influence of objective and subjective factors of life together. In the article the analysis of domestic researches on social and psychological problems of interethnic marriages in our country is given. At present, there are a high need for research on the current characteristics of interethnic marriages in Kazakhstan. The authors studied the problems of marital relations in interethnic marriages, in which the spouses have different types of religious orientation. Empirically identified conflict areas in three types of families, depending on the ratio of types of religious orientation of spouses. The results of the study of mutual relations between spouses in interethnic marriages having a certain type of religious orientation will be of interest to psychologists, social workers, psychotherapists who specialize in assisting the family in dealing with joint life issues, and in carrying out preventive activities among people who have decided to enter into an interethnic marriage. Key words: interethnic family, religious orientation, marital conflicts.